Evaluation and Improvement of User Interface Design in Mobile Delivery Services With User Centered Design Approach and Heuristic Evaluation (Case Study: Kirimaja Application) - Ardhani, Ni Komang Sucitra; Wirdiani, Ni Kadek Ayu; Rusjayanthi, Ni Kadek Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2023)
KirimAja is a mobile-based goods delivery service application that is useful for helping people to send goods easily. This application has several features for sending goods, such as the Sameday Service, Nextday Service, Regular Service, Check Rates, and Check Receipts features. Usability problems in the KirimAja application were found based on observations and responses found in the